THE STRATEGY IN NON-FORMAL EDUCATION : LEARNING OF ISLAMIC EDUCATION BASED ON THE COMMUNITY - Nadila Nur Ratna; Elihami Elihami (JURNAL EDUKASI NONFORMAL, 2021)
The purpose of this research is how to implement a strategy for implementing community-based Islamic religious education, which is included in the stages, approaches and principles of teaching. Methods or ways of studying data in observation, interviews, and documentation studies. The data that has been obtained is then processed in three stages, namely data reduction, data presentation and drawing conclusions. The community tries to work together to provide facilities and infrastructure to support the establishment of this madrasa. In addition, their efforts have also received support from the foundation which provides opportunities for the community to participate in developing madrasas so that the community has a sense of responsibility for the existence of this madrasah. One of the obstacles in this case is the funds and experience from the management of the Foundation, but they continue to communicate with other parties who are more experienced, and the driving factors are the community, government and facilities and infrastructure.